Shape Of Female Stigma On A Breath Of Fresh Air Novel By Amullya Maladi - Muttaqin, Salwa Destria; Sukmawaty, Fenty; Saprudin, Saprudin (Universitas Muria Kudus, 2024)
The object of this study is a novel by a female author with american natinallity who write a novel with indian background story where still a lot of female injustice cases that occur in the novel the tittle is A Breath Of Freash Air. The purposes of this research is to know the shape of female stigma that occur in the noel. This reasearch use qualitative descriptivve methode with objective approach. And from this reasearh the writer find out the shape of female stigma that devided into 4 main points. First is Discrimination, second is self fulfilling prophecy, third is a direct steretype, and the last is threats. From the discrimination it tells how women got the discrimination for how they decide how life they want to be, one of the example is how woman have limitation to decide they want to affairs with their husband or not. At Stereotype cases the woman n the novel got a lot of judgement that just blow up by their oen perception. And for the self fullfilling prophecy, a lot of woman in the novel that indicated with the stigma thought that in the last effect their surrounder. And the last is threats is the effecct of the stigma that exist make ther life in limit and couldnt free to express their expresiion.